PENCATATAN PERKAWINAN YANG SAH MENURUT HUKUM PERDATA YANG BERLANDASAKAN UNDANG-UNDANG TENTANG PERKAWINAN - Prima Resi Putri (Ensiklopedia Social Review, 2021)
Law Number 1 of 1974 concerning Marriage has regulated the registration of marriages, detailed in Article 2 of Law Number 1 of 1974. Provisions regarding this registration are further regulated in detail in Government Regulation Number 9 of 1975 as a regulation for implementing Law Law No. 1/1974. Registration of marriages of those who are Muslim is carried out by Registrar as interpreted in Law Number 32 of 1954. The fact is that in the midst of the community many people still do not register their marriages at the authorized institutions. Resulting in unfavorable consequences for women or the wife and children born. The research method used is normative juridical legal research. The registration of a marriage is intended as an authentic means of proof with the evidence that a marriage can be prevented or canceled. This painting is not a valid marriage or not a marriage that occurs is only for administrative order only. The law requires each marriage to be recorded according to the applicable laws and regulations which means that a marriage is an important social event, therefore it is necessary to be recorded in a record provided specifically for that and to make the event an clear events for the concerned person or others.